Lactobacillus sp as a Probiotic for the Prevention of Clostridium difficile Associated Diarrhea - Ulfa Nur Rohmah; Saskiyanti Ari Andini; Hendrik Prayitno Luawo; Waluyo Waluyo; Yulia Indah Permata Sari (Jurnal Ners, 2019)
Background: Antibiotic treatment can disturb the resistance of the gastrointestinal flora to colonization. This may result in complications, the most serious of which is Clostridium difficile associated diarrhea (CDAD). The aim of this study was to determine the effectiveness of probiotics for the prevention of CDAD.Method: The databases used were Scopus, Proquest, CINAHL, Medline, Pubmed and ScienceDirect, limited to having been published in the last 5 years. A literature review followed the keyword search. The keywords used were probiotics, Clostridium difficile, associated, diarrhea, randomized, control and trial using "AND" and “OR”. Twelve trials with 5102 participants were included. Eight trials reported a preventive effect for CDAD using a mixture of 2 strains of lactobacillus, a mixture of 4 combination strains, a mixture of lactobacillus and Saccharomyces or a mixture of Biﬁdobacterium, Lactobacillus and Saccharomyces.Result: Our findings indicate that probiotics may prevent CDAD. Most probiotics contain a singular strain. The combination with lactobacillus sp was the most effective at preventing CDAD.Conclusion: In addition, 6 out of 8 trials had an in relation to preventing CDAD containing lactobacillus sp. Four studies said that there were some factors that meant that the probiotic could not reduce or prevent the CDAD.